Ability of Manufacturing of Bioformulations using Trichoderma spp for Biological Control of Some Plant Pathogenic Fungi - Ahmed Mshari (Journal of Global Pharma Technology, 2019)
The aims of this study were to Ability of manufacturing of bioformulation using Trichoderma spp, Seven isolation of Trichoderma spp are evaluated as antagonist of five soil-borne fungal diseases, in dual culture, antagonistic activity of T. harzianum (Th3) was showed highest percentage inhibition compare with the other Trichoderma species, which caused 100, 79.16, 69.23, 63.88 and 58.33 % inhibition mycelial growth of Fusarium solani , Fusarium oxysporum f. sp. lycopersici, Fusarium oxysporum f. sp. melonis, Macrophomina phaseolina and Rhizoctonia solani  respectively. Among five groats grains used as substrate for Th3,  Corn substance  has  recorded  the maximum colony forming unit (CFU) produce  27 x 108 g or ml  followed  by  Millet, Barley, Wheat and Rice which record 20,66, 16, 10,33 and 8,66 respectively. Prepared nine different Trichoderma formulations and tested for their shelf life up to 150 day the result showed formulation which has higher shelf life and stress protection was ThT and ThS which record 20.33x108 and 19.66 x108 CFU/ ml respectively and followed by ThG, STCG, CTCG and LTCG which record 11.33 x108, 4.33 x108, 3.33 x108 and 3 x108 CFU/ ml while minimum CFU was  by  ST ,LT, and CT to 1.33 x108 CFU/ ml, 1 x108 CFU/ ml, and 0.66 x108 CFU/ ml respectively.Keywords: Bioformulation, Soil-borne fungal diseases, Antagonistic, Substance, Shelf life.